2001
DOI: 10.1002/jclp.2003
|View full text |Cite
|
Sign up to set email alerts
|

Correspondence between supervisors and trainees in their perception of supervision events

Abstract: The focus of this study is on how the participants in 16 supervisory dyads perceive the content and process in a supervisory session, and on the meaning they attach to supervisory events. A central issue is to what degree the participants in each dyad correspond in their perceptions and evaluation of supervisory events. Another question is how lack of correspondence affects the trainees' experience of satisfaction with the supervision. A majority of the dyads were rated low or moderate in correspondence, and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 19 publications
1
13
0
Order By: Relevance
“…As suggested earlier, therapy and supervision overlap when it comes to alliance (Liese and Beck, 1997;Milne, 2006), and so not surprisingly research indicates that alliance is also an important factor for successful supervision, with some researchers even suggesting that it is the most important aspect of supervision (Ladany, Friedlander and Nelson, 2005;Reichelt and Skjerve, 2002).…”
Section: Illustration One: the Learning Alliancementioning
confidence: 88%
“…As suggested earlier, therapy and supervision overlap when it comes to alliance (Liese and Beck, 1997;Milne, 2006), and so not surprisingly research indicates that alliance is also an important factor for successful supervision, with some researchers even suggesting that it is the most important aspect of supervision (Ladany, Friedlander and Nelson, 2005;Reichelt and Skjerve, 2002).…”
Section: Illustration One: the Learning Alliancementioning
confidence: 88%
“…Our study has also demonstrated the negative potential of supervision, which partly at least can be attributed to the vulnerability of the supervisee, the evaluative function of supervision, the power differential between supervisor and supervisee, to the lack of organisational structure for supervision at the practicum level, and to inadequate supervisor competence. Research on non‐optimal supervision has pointed to conflicts in supervision (Moskowitz & Rupert, ), communication that is restricted or distorted (Yourman & Farber, ), non‐disclosure in supervision (Ladany, Hill, Corbett, & Nutt, ), counter‐productive events (Gray, Ladany, Walker, & Ancis, ), impasses in supervision (Nigam, Cameron, and Leverette () and other unhelpful and potentially harmful experiences in supervision (Reichelt & Skjerve, ).…”
Section: The Spr/crn Study Of Development In Psychotherapistsmentioning
confidence: 99%
“…The supervisor need to be able to provide space for reflection, to be able to refrain from being a psychotherapist, and from telling the psychotherapist how to conduct the clinical work with the patient, and instead focus upon the task of the supervisor, permeated the supervised supervision work. To be able in one's approach as (Braconier, 2005;Reichelt & Skjerve, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Ögren and co-workers (2005) reported evidence that the supervisor's style affected the focus of the supervision, the experience of group climate as well as the perception of how much one learned as a supervisee. In a qualitative interview study of 18 supervision pairs (supervisor-supervisee) Reichelt and Skjerve (2002) found that supervisors with a non-authoritarian style, who were accepting and affirming, were perceived to facilitate a positive development. In the same way, supervisors who both elicited the group's competence and were able to share their own experiences with the supervisees were perceived as contributing to the supervisees' development.…”
Section: The Supervisor As a Model For Learning And Teachingmentioning
confidence: 99%